Enteric viral hepatitis in the Socialist Republic of Vietnam (Southern Vietnam) - Yu. V. Ostankova; A. V. Semenov; D. E. Valutite; E. B. Zueva; E. N. Serikova; A. N. Shchemelev; Hoang Khanh Thu Huynh; E. V. Esaulenko; A. A. Totolian (Журнал инфектологии, 2021)
Aim: To study the hepatitis A (HAV) and hepatitis Е (HEV) prevalence in the Southern region of Vietnam based on the frequency analysis of the antibodies to hepatitis A and E viruses detection in the local population and groups at increased risk of infection.Materials and methods. Serological markers of enteral viral hepatitis were determined in blood serum samples from adults aged 18 to 65 years of three groups: conditionally healthy individuals (n = 397), HIV-infected (n = 316), and patients with chronic viral hepatitis (n = 268). The ELISA method was used for the qualitative detection of anti-HAV IgG, anti-HAV IgM, anti-HEV IgG, anti-HEV IgM.Results. When analyzing the prevalence of anti-HAV IgG in samples obtained from conditionally healthy, HIV-infected, and patients with chronic viral hepatitis, no differences were found between the groups. The incidence of anti-HAV IgG in the general group (n = 981) was 80.1%, in the absence of anti-HAV IgM. There were no gender-age differences in the frequency of anti-HAV IgG in the examined groups. Antibodies anti-HEV IgG in the groups of conditionally healthy, patients with chronic viral hepatitis, and HIV-infected were present in the samples in 36,2%, 33,2%, and 39,8% of cases, respectively. The prevalence of anti-HEV IgM in these groups was 3,27%, 4,1%, and 3,79%, respectively. In the general group (n = 981), anti-HEV IgG was detected in 36,6% of cases, anti-HEV IgM in 3,66%, which corresponds to the prevalence of antibodies to HEV in endemic regions.Conclusion. A high incidence of enteral viral hepatitis markers was shown in residents of South Vietnam, including the groups of conditionally healthy, patients with chronic viral hepatitis, and HIV-infected. There is an obvious need for further studies of the spread extent of hepatitis A and hepatitis E in the Socialist Republic of Vietnam using currently available highly sensitive diagnostic methods, including sequencing of the virus›s nucleotide sequences.